Ultraviolet aging resistant polyurethane material and preparation method thereof

By adding nano-scale inorganic semiconductor materials to the polyurethane materials to absorb ultraviolet energy, the problem of aging of polyurethane materials under ultraviolet light is solved, and the material's ultraviolet aging resistance performance and the expansion of usage scenarios is achieved.

CN119823347APending Publication Date: 2025-04-15CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510052770.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing polyurethane materials are prone to aging under ultraviolet irradiation, resulting in yellowing and mechanical properties degradation. The existing UV aging methods have limitations on raw material use and usage scenarios.

Method used

In the preparation process of polyurethane materials, nano-scale inorganic semiconductor materials are added to absorb ultraviolet energy through their special structures and prevent the damage to the polyurethane molecular structure by ultraviolet rays.

Benefits of technology

Effectively prevent polyurethane materials from aging due to ultraviolet rays, maintain the mechanical properties and color of the materials, and do not restrict the use of raw materials. It is suitable for a wider range of use scenarios, including medical devices and other medical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823347A_ABST
    Figure CN119823347A_ABST
Patent Text Reader

Abstract

The invention discloses an ultraviolet-aging-resistant polyurethane material and a preparation method thereof, relates to the technical field of polyurethane materials, and solves the problems of limitation on raw material use and limitation on use scenes of an existing polyurethane ultraviolet-aging-resistant method. The preparation method comprises the following steps: reacting polyol with polyisocyanate to obtain a prepolymer which is marked as a material A; dispersing a nanoscale inorganic semiconductor material in a chain extender or a mixture of the chain extender, a stabilizer, a pore opening agent and a foaming agent, and uniformly mixing to obtain a material B; uniformly mixing the material A and the material B, uniformly stirring by using a casting machine, and injecting into a mold to obtain the ultraviolet aging resistant polyurethane material. According to the invention, the raw materials of polyurethane are not limited, and the use scene of polyurethane is wider.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyurethane materials, and in particular to a polyurethane material resistant to ultraviolet aging and a preparation method thereof. Background Art

[0002] Polyurethane materials are widely used. For example, polyurethane sponges are widely used in clothing, home furnishing, medical and other industries due to their soft texture, good elasticity and simple preparation method, such as chest pads, shoe materials, sofa cushions, mattresses, pillow cores, medical dressings, etc.; polyurethane elastomers are widely used in runways, basketball courts, tennis courts and other sports venues due to their excellent mechanical properties, good wear resistance and solvent resistance.

[0003] Although polyurethane has many advantages in application, most polyurethanes are prepared with aromatic polyisocyanates as the main raw materials, including toluene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI). Since the amine group is connected to the benzene ring in the molecular structure of the material, ultraviolet radiation will destroy its molecular structure and degrade it, producing a quinone-imide structure, which will cause the material to age, turn dark and yellow, and cause the CN and CO bonds to break, seriously affecting its mechanical properties and physical and chemical properties.

[0004] In view of the above problems, a method for preparing a normal temperature foaming non-yellowing polyurethane sponge is disclosed in Chinese patent document CN105399924A, which uses aliphatic polyisocyanates to replace aromatic polyisocyanates to avoid the yellowing of polyurethane sponges, but the limitations of the raw materials used in this method are too large and are limited to aliphatic polyisocyanates. In addition, a composition for preparing a yellowing-resistant flame-retardant polyurethane sponge and a yellowing-resistant flame-retardant polyurethane sponge are disclosed in Chinese patent document CN117186349A, using a reactive phosphorus-carbon RB antioxidant with active hydrogen to consume the residual NCO group after foaming is completed, avoiding the yellowing, irritating odor, mechanical property degradation and other problems caused by its reaction with water or nitrogen oxides in the air, and the phosphorus-containing functional group can play a flame retardant role. The RB antioxidant prevents the sponge from yellowing by consuming the residual NCO group, but cannot prevent the yellowing caused by ultraviolet light. In order to solve the problem of material aging caused by ultraviolet radiation, some researchers have added organic small molecule UV absorbers to the materials, such as benzophenones, salicylates, triazines and benzotriazoles. Although these UV absorbers can effectively prevent the aging of polyurethane, the biological toxicity of these organic substances will greatly limit the use scenarios of sponges. For example, they are not suitable for skin contact sponges and medical dressings.

[0005] In summary, with regard to the problem of yellowing and degradation of mechanical properties of polyurethane materials caused by ultraviolet irradiation, the existing methods for polyurethane UV resistance still have shortcomings. On the one hand, they are reflected in the restrictions on the use of raw materials, which are limited to aliphatic polyisocyanates; on the other hand, they are reflected in the restrictions on usage scenarios, and are not suitable for direct contact with the skin or medical use. Summary of the invention

[0006] In order to solve the limitations of the above-mentioned existing polyurethane UV aging resistance methods, the present invention provides a polyurethane material resistant to UV aging and a preparation method thereof.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a polyurethane material resistant to ultraviolet aging comprises the following steps:

[0009] S1, reacting polyol and polyisocyanate to obtain a prepolymer, which is recorded as material A;

[0010] S2, dispersing the nano-scale inorganic semiconductor material in the chain extender or in a mixture of the chain extender, the stabilizer, the pore opening agent and the foaming agent, and mixing them evenly, which is recorded as material B;

[0011] S3. Mix material A and material B evenly, stir them evenly with a pouring machine, and inject them into a mold to obtain a polyurethane material resistant to ultraviolet aging.

[0012] Preferably, the reaction temperature in step S1 is 50°C to 90°C.

[0013] Preferably, in step S1, the mass ratio of the polyol to the polyisocyanate is 100:20-60; and the NCO value in the material A is 2%-20%.

[0014] Preferably, the polyol is a diol or a triol selected from polyether polyol, polyester polyol or polycarbonate polyol.

[0015] Preferably, the polyisocyanate is one of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene 1,5-diisocyanate (NDI), p-phenylene diisocyanate (PPDI), xylylene diisocyanate (XDI), 3,3'-dimethyl-4,4'-biphenyl diisocyanate (TODI), triphenylmethane triisocyanate (TTI), 4,4',4'-thiophosphorothioate triphenyl triisocyanate (TPTI), 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, or a mixture of at least two thereof.

[0016] Preferably, the nanoscale inorganic semiconductor material is one or a mixture of at least two of titanium dioxide (TiO2), zinc oxide (ZnO), aluminum oxide (Al2O3), cerium oxide (CeO), tin oxide (SnO2), and silicon nitride (Si3N4).

[0017] Preferably, the mass proportion of the nanoscale inorganic semiconductor material in material B is 0.1% to 20%;

[0018] Preferably, the particle size of the nanoscale inorganic semiconductor material is 5 nm to 500 nm.

[0019] Preferably, the mixing mass ratio of material A to material B is 1:0.05-5.

[0020] The present invention also provides a polyurethane material resistant to ultraviolet aging. The polyurethane material resistant to ultraviolet aging is prepared by applying the above preparation method.

[0021] Compared with the prior art, the specific beneficial effects of the present invention are:

[0022] On the one hand, it is reflected in the restrictions on the use of raw materials, which are limited to aliphatic polyisocyanates; on the other hand, it is reflected in the restrictions on usage scenarios, and is not suitable for direct contact with the skin or medical use.

[0023] The present invention aims to solve the problem of yellowing and mechanical property degradation of polyurethane materials caused by ultraviolet irradiation. Nano-scale inorganic semiconductor materials are added when preparing polyurethane materials. Since the inorganic semiconductor materials have a special structure of valence band and conduction band, when ultraviolet rays irradiate the surface of the semiconductor material, electrons in the valence band absorb energy and are excited to the conduction band, thereby absorbing ultraviolet energy and preventing ultraviolet rays from damaging the molecular structure of the polyurethane.

[0024] The preparation process of the present invention is easy, the operation is simple, the synthesis process is green and environmentally friendly, there is no restriction on the polyurethane raw materials, and the application scenarios of polyurethane are wider. The material has no cytotoxicity and can be used in medical fields such as medical devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the color of the polyurethane material in Examples 1-3 and Comparative Example 1 after being irradiated with ultraviolet light for 16 hours;

[0026] Figure 2 This is a schematic diagram of the color of the polyurethane materials in Examples 4-6 and Comparative Example 2 after being irradiated with ultraviolet light for 16 hours;

[0027] Figure 3 This is a schematic diagram of the color of the polyurethane material in Examples 7-8 and Comparative Example 3 after being irradiated with ultraviolet light for 16 hours;

[0028] Figure 4The tensile stress-strain curves of the polyurethane materials in Examples 1-3 and Comparative Example 1 before ultraviolet irradiation;

[0029] Figure 5 The tensile stress-strain curves of the polyurethane materials in Examples 1-3 and Comparative Example 1 after ultraviolet irradiation;

[0030] Figure 6 The tensile stress-strain curves of the polyurethane materials in Examples 4-6 and Comparative Example 2 before ultraviolet irradiation;

[0031] Figure 7 The tensile stress-strain curves of the polyurethane materials in Examples 4-6 and Comparative Example 2 after ultraviolet irradiation;

[0032] Figure 8 The tensile stress-strain curves of the polyurethane materials in Examples 7-8 and Comparative Example 3 before ultraviolet irradiation;

[0033] Fig. 9 The tensile stress-strain curves of the polyurethane materials in Examples 7-8 and Comparative Example 3 after ultraviolet irradiation;

[0034] Fig.10 These are the cytotoxicity test results of the polyurethane materials in Examples 1 to 8 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0035] In order to make the technical solution of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the specification of the present invention. It should be noted that the following embodiments are only used to better understand the technical solution of the present invention and should not be understood as a limitation to the present invention.

[0036] Example 1.

[0037] Under nitrogen protection, add 30 g of p-phenylene diisocyanate to 100.00 g of anhydrous polyether triol, and stir the mixture at 70° C. until the NCO value is stable and the NCO value is 6.3%, to obtain material A;

[0038] 2 g of titanium dioxide (20 nm) was added to 100.00 g of deionized water, and the mixture was stirred and mixed evenly. Then, 5 g of octadecyl alcohol ether (stabilizer), 20 g of glycerol (chain extender), 10 g of methyl polysiloxane (pore opening agent), and 1 g of sorbitan fatty acid ester (foaming agent) were mixed evenly to obtain material B.

[0039] 50.00 g of the above-mentioned material A and 80.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge resistant to ultraviolet aging.

[0040] Example 2.

[0041] Under nitrogen protection, add 30 g of diphenylmethane diisocyanate to 100.00 g of anhydrous polyester triol, and react with stirring at 70° C. until the NCO value is stable and the NCO value is 6.3%, to obtain material A;

[0042] 6 g of titanium dioxide (100 nm) was added to 100.00 g of deionized water, and the mixture was stirred and mixed uniformly. Then, 5 g of PEG hexadecanol ether (stabilizer), 15 g of glycerol (chain extender), 10 g of polyoxyethylene-polysiloxane (pore opening agent), and 1 g of sorbitan fatty acid ester (foaming agent) were mixed uniformly to obtain material B.

[0043] 50.00 g of the above-mentioned material A and 80.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge resistant to ultraviolet aging.

[0044] Example 3.

[0045] Under nitrogen protection, add 25 g of toluene diisocyanate to 100.00 g of anhydrous polyether triol, and stir the mixture at 70° C. until the NCO value is stable and the NCO value is 5.9%, to obtain material A;

[0046] 4 g of titanium dioxide (200 nm) was added to 100.00 g of deionized water, and the mixture was stirred and mixed uniformly. Then, 5 g of octadecyl alcohol ether (stabilizer), 10 g of glycerol (chain extender), 5 g of polyoxypropylene-polysiloxane copolymer (pore opening agent), and 1 g of sorbitan fatty acid ester (foaming agent) were mixed uniformly to obtain material B.

[0047] 50.00 g of the above-mentioned material A and 90.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge resistant to ultraviolet aging.

[0048] Comparative Example 1 (compared with Example 3, only without adding titanium dioxide).

[0049] Under nitrogen protection, add 25 g of toluene diisocyanate to 100.00 g of anhydrous polyether triol, and stir the mixture at 70° C. until the NCO value is stable and the NCO value is 5.9%, to obtain material A;

[0050] 100.00 g of deionized water, 5 g of octadecyl alcohol ether (stabilizer), 10 g of glycerol (chain extender), 5 g of polyoxypropylene-polysiloxane copolymer (pore opener), and 1 g of sorbitan fatty acid ester (foaming agent) were mixed uniformly to obtain material B;

[0051] 50.00 g of the above-mentioned material A and 90.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge that is not resistant to ultraviolet aging.

[0052] Example 4.

[0053] Under nitrogen protection, 30 g of toluene diisocyanate and diphenylmethane diisocyanate (mass ratio 4:1) were added to 100.00 g of anhydrous polyester triol, and the mixture was stirred at 70°C to react until the NCO value was stable and the NCO value was 6.1%, thereby obtaining material A.

[0054] 2 g of zinc oxide (30 nm) was added to 100.00 g of deionized water, and the mixture was stirred and mixed evenly. Then, 5 g of hexadecanol ether (stabilizer), 10 g of glycerol (chain extender), 5 g of methyl polysiloxane (pore opening agent), and 1 g of sorbitan laurate (foaming agent) were mixed evenly to obtain material B.

[0055] 50.00 g of the above-mentioned material A and 80.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge resistant to ultraviolet aging.

[0056] Example 5.

[0057] Under nitrogen protection, add 30 g of toluene diisocyanate, diphenylmethane diisocyanate and naphthalene 1,5-diisocyanate (mass ratio 8:1:1) to 100.00 g of anhydrous polyether triol, and stir and react at 70°C until the NCO value is stable and the NCO value is 6.0%, to obtain material A;

[0058] 4 g of zinc oxide (200 nm) was added to 100.00 g of deionized water, and the mixture was stirred and mixed uniformly. Then, 5 g of octadecyl alcohol ether (stabilizer), 10 g of glycerol (chain extender), 5 g of polysiloxane (Y-10366) (pore opening agent), and 1 g of sorbitan monooleate (foaming agent) were mixed uniformly to obtain material B.

[0059] 50.00 g of the above-mentioned material A and 90.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge resistant to ultraviolet aging.

[0060] Example 6.

[0061] Under nitrogen protection, add 25 g of naphthalene 1,5-diisocyanate to 100.00 g of anhydrous polyether triol, and stir the mixture at 70° C. until the NCO value is stable and the NCO value is 5.7%, to obtain material A;

[0062] 4 g of zinc oxide (50 nm) was added to 100.00 g of deionized water, and the mixture was stirred and mixed evenly. Then, 5 g of octadecyl alcohol ether (stabilizer), 10 g of glycerol (chain extender), 5 g of polyoxypropylene-ethylene oxide copolyether (pore opening agent), and 1 g of polysorbate 60 (foaming agent) were mixed evenly to obtain material B.

[0063] 50.00 g of the above-mentioned material A and 90.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge resistant to ultraviolet aging.

[0064] Comparative Example 2 (compared with Example 6, only without adding zinc oxide).

[0065] Under nitrogen protection, add 25 g of naphthalene 1,5-diisocyanate to 100.00 g of anhydrous polyether triol, and stir the mixture at 70° C. until the NCO value is stable and the NCO value is 5.7%, to obtain material A;

[0066] 100.00 g of deionized water, 5 g of octadecyl alcohol ether (stabilizer), 10 g of glycerol (chain extender), 5 g of polyoxypropylene-polyoxyethylene copolymer (pore opener), and 1 g of polysorbate 60 (foaming agent) were mixed uniformly to obtain material B;

[0067] 50.00 g of the above-mentioned material A and 90.00 g of the material B were uniformly stirred at high speed using a pouring machine, and injected into a mold for foaming to obtain a polyurethane sponge that is not resistant to ultraviolet aging.

[0068] Example 7.

[0069] Under nitrogen protection, add 50 g of diphenylmethane diisocyanate to 100.00 g of anhydrous polycarbonate diol, and react with stirring at 70° C. until the NCO value is stable and the NCO value is 7.5%, to obtain material A;

[0070] Add 4 g of zinc oxide (30 nm) and titanium dioxide (20 nm) (mass ratio 1:1) to 20 g of butanediol (chain extender), and disperse them evenly by ultrasonication to obtain material B;

[0071] 20g of material A and 1.2g of material B were stirred evenly at high speed, poured into a mold and vulcanized at 110°C for 30 minutes to obtain a polyurethane elastomer resistant to ultraviolet aging.

[0072] Example 8.

[0073] Under nitrogen protection, add 50 g of diphenylmethane diisocyanate to 100.00 g of anhydrous polyester diol, and stir at 70° C. to react until the NCO value is stable and the NCO value is 7.5%, to obtain material A;

[0074] 4 g of titanium dioxide (20 nm) and aluminum oxide (50 nm) (mass ratio 3:2) were added to 20 g of butanediol (chain extender), and ultrasonically dispersed to obtain material B;

[0075] 20g of material A and 1.2g of material B were stirred evenly at high speed, poured into a mold and vulcanized at 110°C for 30 minutes to obtain a polyurethane elastomer resistant to ultraviolet aging.

[0076] Comparative Example 3 (compared with Example 8, only without adding titanium dioxide and aluminum oxide).

[0077] Under nitrogen protection, add 50 g of diphenylmethane diisocyanate to 100.00 g of anhydrous polyester diol, and stir at 70° C. to react until the NCO value is stable and the NCO value is 7.5%, to obtain material A;

[0078] Butanediol (chain extender) is material B;

[0079] 20g of material A and 1.2g of material B were stirred evenly at high speed, poured into a mold and vulcanized at 110°C for 30 minutes to obtain a polyurethane elastomer that was not resistant to UV aging.

[0080] Effect example.

[0081] The polyurethane materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were placed in an ultraviolet aging box for 16 hours, and the yellowing of the polyurethane materials was observed after being taken out, and the changes in mechanical properties of the materials before and after ultraviolet aging were tested. In addition, the cytotoxicity of the polyurethane materials was tested in accordance with GB / T16886.5-In vitro cytotoxicity test standard.

[0082] After testing, the polyurethane materials of Examples 1-3 and Comparative Example 1 showed a color change after being irradiated with UV light for 16 hours. Figure 1 The polyurethane materials of Examples 4-6 and Comparative Example 2 showed a different color after being irradiated with UV light for 16 hours. Figure 2 The polyurethane materials of Examples 7-8 and Comparative Example 3 showed a different color after being irradiated with UV light for 16 hours. Figure 3 ; Figure 1 to Figure 3 It can be proved that polyurethane materials added with inorganic semiconductor materials have the ability to resist yellowing caused by ultraviolet aging.

[0083] The mechanical properties test results of the material before and after UV aging are shown in Table 1.

[0084] Table 1

[0085]

[0086]

[0087] Among them, the tensile stress-strain curves of the polyurethane materials in Examples 1-3 and Comparative Example 1 before ultraviolet irradiation are shown in Figure 4 , the tensile stress-strain curve after UV irradiation is shown in Figure 5 ; The tensile stress-strain curves of the polyurethane materials in Examples 4-6 and Comparative Example 2 before ultraviolet irradiation are shown in Figure 6 , the tensile stress-strain curve after UV irradiation is shown in Figure 7 ; The tensile stress-strain curves of the polyurethane materials in Examples 7-8 and Comparative Example 3 before ultraviolet irradiation are shown in Figure 8 , the tensile stress-strain curve after UV irradiation is shown in Fig. 9 ;

[0088] Figures 4 to 9 The results in Table 1 show that the polyurethane material with added inorganic semiconductor materials has UV aging resistance, avoiding the problem of mechanical property degradation caused by UV irradiation.

[0089] Fig.10 The cytotoxicity test results of the polyurethane materials in Examples 1 to 8 and Comparative Examples 1 to 3 are shown. It can be proved that the polyurethane materials added with inorganic semiconductor materials are non-cytotoxic and can be used in the field of medical devices. In summary, the addition of inorganic semiconductor materials can effectively improve the UV aging resistance of polyurethane materials, and there is no restriction on polyurethane raw materials, and the application scenarios are more extensive.

Claims

1. A method for preparing a polyurethane material resistant to ultraviolet aging, characterized in that: The steps include: S1, reacting polyol and polyisocyanate to obtain a prepolymer, which is recorded as material A; S2, dispersing the nano-scale inorganic semiconductor material in the chain extender or in a mixture of the chain extender, the stabilizer, the pore opening agent and the foaming agent, and mixing them evenly, which is recorded as material B; S3. Mix material A and material B evenly, stir them evenly with a pouring machine, and inject them into a mold to obtain a polyurethane material resistant to ultraviolet aging.

2. The method for preparing the ultraviolet aging resistant polyurethane material according to claim 1, characterized in that: The reaction temperature in step S1 is 50°C to 90°C.

3. The method for preparing the polyurethane material resistant to ultraviolet aging according to claim 1, characterized in that: The mass ratio of the polyol to the polyisocyanate in step S1 is 100:20-60; the NCO value in the material A is 2%-20%.

4. The method for preparing the polyurethane material resistant to ultraviolet aging according to claim 1, characterized in that: The polyol is a diol or a triol, selected from polyether polyol, polyester polyol or polycarbonate polyol.

5. The method for preparing the polyurethane material resistant to ultraviolet aging according to claim 1, characterized in that: The polyisocyanate is one of toluene diisocyanate, diphenylmethane diisocyanate, naphthalene 1,5-diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, 3,3'-dimethyl-4,4'-biphenyl diisocyanate, triphenylmethane triisocyanate, 4,4',4'-thiophosphoric acid triphenyl triisocyanate, and 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, or a mixture of at least two thereof.

6. The method for preparing the polyurethane material resistant to ultraviolet aging according to claim 1, characterized in that: The nanometer-scale inorganic semiconductor material is one of titanium dioxide, zinc oxide, aluminum oxide, cerium oxide, tin oxide, and silicon nitride, or a mixture of at least two of them.

7. The method for preparing the polyurethane material resistant to ultraviolet aging according to claim 1, characterized in that: The mass proportion of the nano-scale inorganic semiconductor material in the B material is 0.1% to 20%.

8. The method for preparing the polyurethane material resistant to ultraviolet aging according to claim 1, characterized in that: The particle size of the nano-scale inorganic semiconductor material is 5nm to 500nm.

9. The method for preparing the polyurethane material resistant to ultraviolet aging according to claim 1, characterized in that: The mixing mass ratio of the material A to the material B is 1:0.05-5.

10. A polyurethane material resistant to ultraviolet aging, characterized in that: The method is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing no-yellowing polyurethane sponge capable of being foamed at normal temperature

    CN105399924A

  • Composition for preparing anti-yellowing flame-retardant polyurethane sponge and anti-yellowing flame-retardant polyurethane sponge

    CN117186349A

  • Inorganic nanoparticles-modified polyurethane sponge mask material, and preparation method and application thereof

    CN102190882A

  • Anti-aging polyurethane sole material

    CN103289048A

  • Environment-friendly high elasticity and yellowing resisting polyurethane sponge and preparation method thereof

    CN108359074A